Lidar observation and model simulation of a volcanic-ash-induced cirrus cloud during the Eyjafjallajökull eruption - Rolf, C.; Krämer, M.; Schiller, C.; Hildebrandt, M.; Riese, M. (Atmospheric Chemistry and Physics, 2012)
Heterogeneous ice formation induced by volcanic ash from the Eyjafjallajökull volcano eruption in April 2010 is investigated based on the combination of a cirrus cloud observed with a backscatter lidar over Jülich (western Germany) and model simulations along backward trajectories. The microphysical properties of the cirrus cloud could only be represented by the microphysical model under the assumption of an enhanced number of efficient ice nuclei originating from the volcanic eruption. The ice nuclei (IN) concentration determined by lidar measurements directly before and after cirrus cloud occurrence implies a value of around 0.1 cm−3 (in comparison normal IN conditions: 0.01 cm−3). This leads to a cirrus cloud with rather small ice crystals having a mean radius of 12 μm and a modification of the ice particle number (0.08 cm−3 instead of 3 × 10−4 cm−3 under normal IN conditions). The effectiveness of ice nuclei was estimated by the use of the microphysical model and the backward trajectories based on ECMWF data, establishing a freezing threshold of around 105% relative humidity with respect to ice in a temperature range from −45 to −55 °C . Only with these highly efficient ice nuclei was it possible for the cirrus cloud to be formed in a slightly supersaturated environment.